The Influence of Organizational Culture on Employee Retention: A Case of Google - Zulfan, Gilang; Kee, Daisy Mui Hung; Khor, Tze Win; Lee, Sze Yin; Ali, Hayder Jabbar; Hanan, Alsharqawi; Akansha, Verma (Journal of The Community Development in Asia, 2020)
Google’s organizational culture is one of the main reasons it has cemented its place as the biggest player in the current age of information technology, rapid digital growth, and in the fourth Industrial Revolution which includes the Internet of Things (IoT), virtual reality (VR) and artificial intelligence (AI). This paper investigates how a healthy workplace culture cultivates the best and retains the best and talented employees in the field. How the mission, core values, and flexibility resonate with the employees in building the culture. The paper presents the influence of organizational culture on employee retention in Google. The paper analyzes the pros and cons of such a culture and its impact on the company. The paper concludes with implication and recommendation to the companies and business leaders around the world.